The Enigma game - Wein, Elizabeth (Hyperion, 2020)
Told in multiple voices, fifteen-year-old Jamaican Louisa Adair uncovers an Enigma machine in the small Scottish village where she cares for an elderly German woman, and helps solve a puzzle that could turn the tide of World War II.